39th Aerospace Sciences Meeting and Exhibit 2001
DOI: 10.2514/6.2001-1129
|View full text |Cite
|
Sign up to set email alerts
|

Detonation initiation studies and performance results for pulsed detonation engine applications

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Dayton, OH 45440Abstract An in-house computational and experimental program to investigate and develop an air breathing pulse detonation engine (PDE) that uses a practical fuel (kerosene based, fleet-wide use, "JP" type) is curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 3 publications
(2 reference statements)
2
56
0
1
Order By: Relevance
“…The PDEs are classified as air-breathing PDEs [19][20][21][22] or pulse detonation rocket engines (PDREs) [23][24][25]. With a simplified PDE setup, that is, when viscosity and heat conduction are neglected and a tube-geometry combustor is fully filled with propellant at ambient pressure and a detonation wave is initiated instantaneously, a PDRE using H 2 -O 2 propellant can achieve a specific impulse of 190 sec and an air-breathing PDE using hydrogen fuel can achieve a specific impulse of 4200 sec, as achieved in experiments by Schuer et al [26], Cooper et al [27] and…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The PDEs are classified as air-breathing PDEs [19][20][21][22] or pulse detonation rocket engines (PDREs) [23][24][25]. With a simplified PDE setup, that is, when viscosity and heat conduction are neglected and a tube-geometry combustor is fully filled with propellant at ambient pressure and a detonation wave is initiated instantaneously, a PDRE using H 2 -O 2 propellant can achieve a specific impulse of 190 sec and an air-breathing PDE using hydrogen fuel can achieve a specific impulse of 4200 sec, as achieved in experiments by Schuer et al [26], Cooper et al [27] and…”
Section: Introductionmentioning
confidence: 92%
“…However, these studies were single-shot experiments. In contrast, in multi-shot thrust measurement experiments [26,45,46], the relationship between the DDT distance and the thrust performance was not investigated.…”
mentioning
confidence: 99%
“…(3) for 0.0676 < V /V 0 < 1 and Eq. (4) for 0 < V /V 0 < 0.0676, is compared to multicycle experiments by Schauer et al 9 in hydrogen-air mixtures (Fig. 3).…”
Section: Comparisons With Partial-fill Correlationmentioning
confidence: 99%
“…Previous studies of the application of MHD to engine inlets have shown that the MHD action increases flow compression and mass flow rate. 4,8,9 However, the resulting improvements in flow parameters were incremental. It was also proposed to use MHD to decelerate the flow in front of the combustion chamber of the scramjet engine, with subsequent acceleration of the flow after the chamber.…”
Section: Introductionmentioning
confidence: 99%
“…The general effect of this parameter has been demonstrated elsewhere. 5,6 In terms of stand-alone thrust devices, reducing Reactant Fraction increases fuel specific impulse at the expense of specific thrust.…”
Section: Operational Mode Parametersmentioning
confidence: 99%